QSR Study Between Octanol-Water Partitioning Coefficients, Total Biodegradation of Barbiturates and Randic Index - Taherpour, Avat (Arman); Taherpour, Zhiva; Taherpour, Arezo; Farajie, Mehrak (Asian Journal of Chemistry, 2010)
Barbiturates are primarily used for insomnia and preoperative sedation. These drugs contain a “balance” of hydrophilic (2,4,6-pyrimidinetrione ring structure) and lipophilic (5,5'-substituents) functionality. Because of these property, the insertion of these compounds in fatty tissue of body has a high importance in medicinal studies. The octanol-water partition coefficient (Kow) is a measure of the equilibrium concentration of a compound between octanol and water that indicates the potential for partitioning in to soil organic matter (i.e., a high Kow indicates a compound which will preferentially partition into soil organic matter rather than water). Biodegradation (TBd) is another useful and important factors in chemical and biochemical studies. It needs to use the effective and useful mathematical methods for making good concern between several data in chemistry and biochemistry. Graph theory is a sub discipline of mathematics that is closely related to both topology and combinatory concepts. Here, was used Randic index (χ) for molecular description of structure-property relationship studies for the logarithm of calculated octanol-water partitioning coefficients and total biodegradation [log Kow and TBd (mol/h), respectively] in barbiturate compounds. The Randic index (χ) one of the useful indices for examination of QSAR studies. The interesting results of concerning among log Kow, TBd and τa index for this compounds are presented.